Isolated intracranial Rosai–Dorfman disease mimicking petroclival meningioma in a child: Case report and review of the literature. Issue 47 (November 2017) - Yang, Xiang; Liu, Jiagang; Ren, Yanming; Richard, Seidu A.; Zhang, Yuekang
Abstract: Rationale: Rosai –Dorfman disease (RDD) is a rare, idiopathic, and non-neoplastic histioproliferative disease with distinctive entity of unknown etiology. Central nervous system (CNS) RDD is uncommon, hence, isolated intracranial RDD is extremely rare. So far only 6 cases of CNS RDD with the lesions originating from petroclival region have been reported. We present a case of isolated intracranial RDD mimicking petroclival meningioma. Patient concerns: A 14-year-old girl was admitted at our hospital with a 3-month history of dizziness, slowly progressing headache, and 2-month history of instability in walking. Cranial nerve deficits, including left facial paralysis, left facial numbness and left hearing loss, were evident on examination. Diagnoses: Initial diagnosis of petroclival meningioma was made according to preoperative magnetic resonance imaging. Interventions: The lesion was resected subtotally and pathology confirmed RDD. The patient received gamma-knife treatment for the residual lesion. Outcomes: The patient recovered well and the residual lesion significantly retrogressed on follow-up images. Lessons: Preoperative diagnosis of petroclival RDD is full of challenges. Although surgical resection of lesions is an effective treatment option, total resection is not highly recommended because the surgery-related defect must be minimal. Patient with residual lesion can be put on steroid therapy and/or radiotherapy, especially for IgG4 positive subset of RDD.